What's the Rush? Tort Laws and Elective Early-term Induction of Labor. (December 2016) - Roth, Louise Marie
Tort laws aim to deter risky medical practices and increase accountability for harm. This research examines their effects on deterrence of a high-risk obstetric practice in the United States: elective early-term (37–38 weeks gestation) induction of labor. Using birth certificate data from the Natality Detail Files and state-level data from publicly available sources, this study analyzes the effects of tort laws on labor induction with multilevel models (MLM) of 665, 491 early-term births nested in states. Results reveal that caps on damages are associated with significantly higher odds of early-term induction and Proportionate Liability (PL) is associated with significantly lower odds compared to Joint and Several Liability (JSL). The findings suggest that clinicians are more likely to engage in practices that defy professional guidelines in tort environments with lower legal burdens. I discuss the implications of the findings for patient safety and the deterrence of high-risk practices.